Identification and characterization of different accessions of itchgrass (Rottboellia cochinchinensis) - Alves, PLCA; Bachega, M. F.; Moro, JR; Lemos, MVF; Alves, ECC; Silva, MAS; Moro, F. V. (Weed Sci Soc Amer, 2003)
Studies were conducted to identify and characterize different accessions of itchgrass. Seeds were collected in the counties of Aramina, Campinas, Dumont, Igarapava, Jaboticabal, and Ribeirao Preto, all in the state of São Paulo, Brazil. Accessions were characterized based on dimensions of their stomata, stomatal index (SI), and length and width of their seed (caryopses and husk). Chromosome number and length also were determined, and accessions were further differentiated using molecular markers (polymerase chain reaction [PCR]). Itchgrass from Ribeirao Preto had much longer and narrower seeds than those from the other locations, and their husks were longer as well. Accessions had similar SIs, both on the abaxial and adaxial leaf surfaces. Stomata from Campinas and Igarapava accessions were longer and wider, whereas those from Dumont and Ribeirao Preto were similar and smaller than all others. The accession from Ribeirao Preto is diploid (2n = 20); the rest are polyploid, with the total length of chromosomes smaller than all others. These differences were confirmed by molecular differentiation (PCR).
Keywords: chromosomes; morphology; biotypes